PENGARUH HUMOR POLITIK TERHADAP REPUTASI KOMIKA MELALUI PERSEPSI GENERASI Z DALAM PENYAMPAIAN STAND-UP COMEDY - Febry, Vanessa; Latupeirissa, Jonathan Jacob Paul; Permatasari, Ni Putu Intan; Pratiwi, Nuning Indah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The use of political humor has transformed the way political communication is conducted in Indonesia, particularly among Generation Z. Stand-up comedy performances by comedians have become an effective form of political communication, where humor is used to deliver social and political critism. The rapid development of information technology and social media also supports the dissemination of such content. This makes political information and political-themed content, such as stand-up comedy addressing political issues, easily accessible to the public. This study aims to examine the influence of political humor on the reputation of comedians, consediering Generation Z’s perception as a mediating variable in the delivery of stand-up comedy. This research uses a quantitative method involving 100 respondents selected through accidental sampling. Data was collected via questionnaires and analyzed using partial least squares. Result shows that political humor has a significant positive influence on the reputation of comedians through the perception of Generation Z. Generation Z’s perception acts as mediator that strenghthens the relationship berween political humor and a comedian’s reputation. These findings highlight the importance of understanding the audience when delivering political humor, as well as its impact on the public image of comedians. This study is expected to provide insights for comedians and entertainment industry players in crafting stand-up comedy material that not only entertains, but also builds a positive reputation among Generation Z.